Synthesis of xylanase gene from bacillus pumilus PJ19 - 192091 Lee, Chiang Hung (Sekudai : UTM, 1999)
Project Paper (Bachelor of Chemical Engineering (Bioprocess)) - Universiti Teknologi Malaysia, 1999